THE EFFECT OF SOCIAL MEDIA ORIENTATION ON MARKETING PERFORMANCE THROUGH VILCHIC BRAND IMAGE - Lilis Suryani; Syahmardi Yacob; Musnaini Musnaini (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This study aims to determine the influence of Social Media Orientation, Marketing Performance, and Brand Image. This research uses a quantitative descriptive method with Partial Least Square (PLS) Professional analysis tool. The subjects of this research are consumers who use vilchic masks in Jambi and outside the city of Jambi. The sampling technique used is purposive sampling. The number of samples used in this study amounted to 125. The results of this study indicate that social media orientation does not affect the marketing performance of vilchic companies. Social media has a significant impact on brand image, and brand image can affect the marketing performance of vilchic companies. The brand image variable in this study can influence or mediate between the marketing performance variables and the social media orientation, meaning that this research is full mediation. The findings of this study contribute that Brand Image is an essential factor in seeing the sales performance of vilchic companies.